Four-Character Idioms and the Rhetoric of Japanese Shakespeare Translation - Gallimore, Daniel (Multicultural Shakespeare: Translation, Appropriation and Performance, 2021)
Yoji jukugo are idioms comprised of four characters (kanji) that can be used to enhance the textuality of a Japanese Shakespeare translation, whether in response to Shakespeare’s rhetoric or as compensation for the tendency of translation to be carried out at a lower textual register than the source. This article examines their use in two translations each of Julius Caesar by Matsuoka Kazuko (2014) and Fukuda Tsuneari (1960) and of The Merry Wives of Windsor by Matsuoka (2001) and Odashima Yūshi (1983); in both cases Matsuoka uses significantly more yoji jukugo than her predecessors. In the Julius Caesar translations their usage is noticeable in the set speeches by Antony and Brutus in 3.2, and commonly denote baseness or barbarity. In the Merry Wives translations they commonly denote dissolute behaviour, often for comic effect, and can even be used malapropistically in the target language.